Wire Electrochemical Machining employing newly developed tungsten micro wire with repeatedly similar cross sectional variations. (February 2022) - Debnath, S.; Masanta, M.; Bhattacharyya, B.
Abstract: Wire Electrochemical Machining (WECM) is a newer fabrication process. Here, research works are available regarding process fundamentals, flushing mechanisms and fabrication of new features in different work materials. But attempts are few regarding fabrication of wire itself where there has been no research attempt to form geometries on wire. Hence, this research work is directed towards in situ fabrication of wire with repeated geometries such as repeatedly similar cross sectional variations using reverse electrochemical etching via a unique methodology. Here, tungsten wire of diameter 50 μm has been taken as parent wire. After fabrication of such wire, investigation has been carried out to analyze its fruitful application in WECM in enhancing the surface quality and homogeneity of microfeatures compared to smooth cylindrical wire. Enhanced surface quality and homogeneity is the result of combined effect of electrochemical machining as well as polishing. The surface average and roughness of sidewall of microslit fabricated by WECM employing wire with repeatedly similar cross sectional variations has reduced to 1.44 μm and 0.09 μm respectively, whereas, the standard deviation of slit width has reduced to approximately 5.5 μm. Furthermore, investigation has been carried out to enhance the dimensional accuracy of fabricated wire by employing piezo-electric vibrations. The influence of PZT vibration amplitude and frequency has also been analyzed. Here, highly homogenous and cylindrical smaller cross sections of wire fabricated with best process parameter and PZT settings have showed standard deviation of 1.5 μm only. The average diameter is approximately 33 μm that has been reduced from parent wire of diameter 50 μm. Graphical abstract: Unlabelled Image Highlights: Repeated geometries on tungsten micro wire were achieved using thin electrolyte film during reverse electrochemical etching. The fabricated wire, being reciprocated and travelled during WECM, provided combined effect of machining and polishing. This resulted in better homogeneous dissolution, surface quality and homogeneity in comparison with smooth cylindrical wire. Implemented PZT vibrations during wire fabrication removed reverse tapering and restricted sudden decrease in diameters.